Strategic control : a problem looking for a solution. - Asch, David (1992)
Attempts to address some of the key aspects of the complex issues surrounding strategic control. Control as a generic concept and process is considered first. Different types of strategic control are explored in a discussion of strategic momentum control and strategic leap control. The findings of some empirical research are discussed and barriers to strategic control identified. The article concludes by briefly looking at the problems associated with the use of financial measures for strategic control.